Effect of Aqueous Warionia saharae Extract on Lipid and Glucose Metabolism in Normal and Diabetic Rats - Hebi, Morad; Haidani, Ahmed E.; Eddouks, Mohamed (Natural Products Journal, The, 2020)
Objective: The aim of the study was to evaluate the hypolipidemic and antioxidant properties of aerial parts aqueous extract of Warionia saharae (APAE of W. saharae) in normal and streptozotocin (STZ) induced-diabetic rats. Additionally, the quantitative and qualitative analysis for the presence of different phytochemical constituents in the APAE of W. saharae was performed. Methods: The effects of oral administration of APAE of W. saharae (5 mg/kg) on the plasma Total Cholesterol (TC) and triglyceride (TG) levels were measured in both normal and diabetic rats. Moreover, the antioxidant capacity was realized by the method of DPPH. Total polyphenol as x of the APAE of W. saharae were determined. Results: APAE of W. saharae showed a strong hypolipidemic and antihyperglycemic effects both in normal and in STZ induced diabetic rats. On the other hand, APAE of W. saharae showed a potent antioxidant activity and revealed inhibitory activity. Moreover, the quantitative determination of total polyphenol and flavonoid contents showed high contents of these phytochemicals. Concerning the qualitative analysis several classes of chemicals have been found. Conclusion: APAE of W. saharae (5 mg/kg) shows the potential cholesterol and glucose lowering activity as well as antioxidant properties in both normal and STZ-induced diabetic rats.
Keywords: antioxidant